Dropouts in sublingual allergen immunotherapy trials – a systematic review. Issue 5 (27th March 2014) - Makatsori, M.; Scadding, G. W.; Lombardo, C.; Bisoffi, G.; Ridolo, E.; Durham, S. R.; Senna, G.
Abstract Participant dropouts can reduce the power of allergen immunotherapy clinical trials. Evaluation of the dropout rate and reasons for dropout are important not only in the planning of clinical studies but are also relevant for adherence to immunotherapy in daily clinical practice. A systematic review was carried out in order to establish the overall dropout rate among published double‐blind, placebo‐controlled randomized clinical trials of sublingual immunotherapy for respiratory allergic diseases. Dropouts were analysed in regards to allergen, formulation, treatment schedule, participant age, study size, number of centres and type of allergic disease. Relative dropout rates in placebo and active groups as well as reasons for dropout were also assessed. A total of 81 studies, comprising 9998 patients, were included. Dropout rates in sublingual immunotherapy controlled studies do not appear to be a major problem with a composite dropout percentage of 14% (95% CI:11.9–16). Furthermore, they are not different for active compared to placebo‐treated participants. This lends support to the positive clinical outcomes seen in meta‐analyses of these trials.